2020
DOI: 10.1101/2020.11.25.20238386
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Explainable Machine Learning models for Rapid Risk Stratification in the Emergency Department: A multi-center study

Abstract: IntroductionRisk stratification of patients presenting to the emergency department (ED) is important for appropriate triage. Using machine learning technology, we can integrate laboratory data from a modern emergency department and present these in relation to clinically relevant endpoints for risk stratification. In this study, we developed and evaluated transparent machine learning models in four large hospitals in the Netherlands.MethodsHistorical laboratory data (2013-2018) available within the first two h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…age and sex) and the results of laboratory tests available within the first two hours of ED presentation to create an individualized, precise and rapid risk estimation of 31-day mortality. The RISK INDEX has externally been validated in three other hospitals, showing high prognostic accuracy (AUC ranging from 0.88 to 0.98) [16]. To the best of our knowledge, the MARS-ED study is the first prospective, randomized study to investigate the clinical impact of a ML based prediction model in the ED.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…age and sex) and the results of laboratory tests available within the first two hours of ED presentation to create an individualized, precise and rapid risk estimation of 31-day mortality. The RISK INDEX has externally been validated in three other hospitals, showing high prognostic accuracy (AUC ranging from 0.88 to 0.98) [16]. To the best of our knowledge, the MARS-ED study is the first prospective, randomized study to investigate the clinical impact of a ML based prediction model in the ED.…”
Section: Discussionmentioning
confidence: 99%
“…However, the generalizability of the results of our study is enhanced because we are performing a broadly designed trial in which all patients who enter the ED for assessment and treatment by an internal medicine specialist can be included, and in which there is also a delayed consent pathway to include patients who are temporarily unable to provide informed consent. Furthermore, a recent multicenter validation study showed that the RISK INDEX can be adapted to each medical center's population [16]. In that study in four EDs, the RISK INDEX showed very high discriminatory performance (AUC ranging from 0.88 to 0.98), indicating that the RISK INDEX is applicable despite local differences in patient demographics.…”
Section: Limitationsmentioning
confidence: 99%
See 3 more Smart Citations